2019
DOI: 10.1155/2019/7361826
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Lipocalin-2 Concentrations with Psoriasis and Psoriatic Arthritis: An Updated Meta-Analysis

Abstract: Objectives. The purpose of this study was to explore the association of serum lipocalin-2 concentrations with psoriasis and psoriatic arthritis (PsA). Methods. A systematic search of studies on the association of serum lipocalin-2 concentrations with psoriasis/PsA was conducted in PubMed, Web of Science, Elsevier ScienceDirect, and Cochrane Library. Eventually, 8 eligible studies were included. The strength of association between serum lipocalin-2 concentrations and psoriasis/PsA was assessed by pooled standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…This study identified a significant increase in serum and tissue LCN2 of patients when compared with healthy controls. Our results regarding serum LCN2 are in accordance with few previous studies 2,3,7,8 . The role of LCN2 in psoriasis remains unclear.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study identified a significant increase in serum and tissue LCN2 of patients when compared with healthy controls. Our results regarding serum LCN2 are in accordance with few previous studies 2,3,7,8 . The role of LCN2 in psoriasis remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…More recently LCN2 was linked to atherosclerosis. In both atherosclerotic plaques and the intima of injured vessels, LCN2 localizes with matrix metalloproteinase‐9, a key protease in inflammation and atherosclerosis 2–4 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, Baran et al noticed a significant positive correlation between irisin in psoriasis patients and laboratory parameters of inflammation, namely CRP and ESR, as well as lipocalin-2 [ 26 ], a protein secreted mainly by activated neutrophils that has been associated with inflammatory responses and described as elevated in psoriasis [ 31 ]. The results obtained by these authors suggested that irisin should not be considered an indicator of metabolic conditions, severity of psoriasis or efficacy of antipsoriatic treatment but might be a marker of inflammation in psoriatic patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides cytokines, chemoattractant molecules such as S100a9, Lcn2 and Tslp are increased in DKO* mice and in patients. 9,31,[39][40][41] These molecules are considered antimicrobial peptides, and one of the multiple functions is to attract immune cells towards lesional skin, such as neutrophils to kill pathogens. 42 Interestingly, neutrophils were highly recruited in psoriasis plaques and other neutrophil- Studies in vitro confirmed that FIB-116 acts directly on stimulated keratinocytes inhibiting their proliferation and pro-inflammatory response associated with TSLP, an important mediator in psoriasis.…”
Section: Discussionmentioning
confidence: 99%